Design, synthesis, molecular modeling and biological evaluation of novel diaryl heterocyclic analogs as potential selective cyclooxygenase-2 (COX-2) inhibitors - Deema A. Al-Turki; Mohamed A. Al-Omar; Laila A. Abou-zeid; Ihsan A. Shehata; Mohammed S. Al-Awady (Elsevier, 2017)
New series of 3,4-diaryl-2-thioxoimidazolidin-4-ones and 3-alkylthio-4,5-diaryl-4H-1,2,4-triazoles were designed, synthesized and evaluated for their activity as anti-inflammatory agents. Compounds 20, 21, 23 and 34 are highly selective inhibitors of COX-2 enzyme at a concentration of 100 mM relative to celecoxib, the standard reference. (±)-3-(4-Phenoxy-phenyl)-5-phenyl-2-thioxoimidazolidin-4-ones 23 exhibited the most active anti-inflammatory agent.